The Effect of Sesame Butter – Supplemented Breakfast in Comparison to Common Breakfast on the Severity of Primary Dysmenorrhea in the Students of Ahvaz Jundishapur University of Medical Sciences - Fatemeh Haidari; Majid Mohammad Shahi; Esmat Shirbeigi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Primary dysmenorrhea is a common medical disorder in young women. The non-steroidal anti-inflammatory drugs are considered to be the common agents to treat it. Regarding the anti-inflammatory effects of sesame, the present study was conducted to evaluate the effect of sesame butter-supplemented breakfast in comparison to common breakfast on the severity of primary dysmenorrhea in the students of Ahvaz University of Medical Science. Subjects and Methods: In this clinical trial, 60 female single students (18-25 years old) with dysmenorrhea were randomly divided into case and control groups. Subjects in the case group were treated with sesame butter-supplemented breakfast from 2 days before menses to 3 days after it, for 2 consecutive months. In the control group, the subjects were asked to eat common breakfast. Menstrual, anthropometric and dietary parameters were assessed and analyzed statistically. Results: At the baseline, there were no significant differences in menstrual characteristics, anthropometric indices and dietary intake data between the two groups. Eating sesame supplemented breakfast for 5 days in two consecutive menses reduced the severity of primary dysmenorrhea significantly (p<0.05).Conclusion: It seems that sesame butter could be effective in alleviating of the severity of dysmenorrhea. However, measurement of serum and tissue levels of prostaglandins and inflammatory factors is suggested to clarify its possible mechanisms.